Curriculum mapping charting the course for content - Association for Supervision and Curriculum Development (Virgina : Association for Supervision and Curriculum Development, 1999)
Consist of two videotape. the first videotape describes the purpose and possibilities of mapping and presents an overview of the mapping process as it has occured in schools. While the second videotape focus on revising the maps using esential quustion, precision skills, development assessments, and computer technology.
episode 1. The essentials of mapping - episode 2. Putting mapping to work
Keywords: Curriculum planning